AAA+ proteins: diversity in function, similarity in structure. (22nd January 2008) - Snider, Jamie; Houry, Walid A.
Abstract : The AAA+ (ATPases associated with various cellular activities) superfamily of proteins represents a distinct lineage of the larger class of P-loop NTPases. Members of this superfamily use the power of nucleotide binding and hydrolysis to direct molecular remodelling events. All AAA+ proteins share a common core architecture, which, through various sequence and structural modifications, has been adapted for use in a remarkably diverse range of functions. The following mini-review provides a concise description of the major structural elements common to all AAA+ proteins in the context of their mechanistic roles. In addition, the evolutionary and functional diversity of this superfamily is described on the basis of recent classification studies.